Homens e anticoncepção: duas gerações de «camadas médias» no Brasil - Maria Coleta Oliveira; Elisabete Bilac; Malvina Muszkat (Cahiers des Amériques Latines, 2002)
The objective of this work is to understand masculine attitudes and practices concerning contraception. In adopting a gender perspective, we attempt to understand the logical interpretation of men concerning their reproductive lives, in identifying the elements which influence their reasoning, the socio-cultural matrix which is at the base of their efficacy and their reproductive practice. The idea that contraception is a women’s affair models and regulates the fecundity of men in the two generations studied. The results point towards several practical recommendations: the necessity of an education programme aimed at men, the importance of the theme of double-protection in campaigns aimed at increasing the use of condoms, research into contraceptive choices, and into the resistance to and continuity of use of the intrauterine device (I.U.D). Finally, faced with the general criticism of contraceptive pills, we recommend research into the tolerance to existing products on the Brazilian market aimed at responding to women’s needs.